Commentary on Harrison: "Social Mechanisms of Stylistic Change" - Burgess, Samantha (Empirical Musicology Review, 2021)
This is a review of Harrison's (2021) paper "Social Mechanisms of Stylistic Change: A Case Study from Early 20th-Century France." In this study, Harrison found that the Apaches, a group of composers known for pushing stylistic boundaries in 20th-century France, employed slightly more instances of notated meter change in their music than a control group of their peers, but that the use of notated meter change also depended on other factors such as composers' generational membership. This commentary primarily explores Harrison's methodologies: while the stringent definitions Harrison defines for each variable in her studies allow for specificity in the statistical analyses, they leave out a large portion of perceptually relevant data that would lend greater musicological generalizability to the results presented.